Evolution of Principle and Practice of Electrodeposited Thin Film: A Review on Effect of Temperature and Sonication - A. Mallik; B. C. Ray (International Journal of Electrochemistry)
This review discusses briefly the important aspects of thin films. The introduction of the article is a summary of evolution of thin films from surface engineering, their deposition methods, and important issues. The fundamental aspects of electrochemical deposition with special emphasis on the effect of temperature on the phase formation have been reviewed briefly. The field of sonoelectrochemistry has been discussed in the paper. The literature regarding the effects of temperature and sonication on the structure and morphology of the deposits and nucleation mechanisms, residual stress, and mechanical properties has also been covered briefly.